2012
DOI: 10.1088/1674-4926/33/9/093002
|View full text |Cite
|
Sign up to set email alerts
|

A nanostructured copper telluride thin film grown at room temperature by an electrodeposition method

Abstract: Copper telluride onion flower like microstructures, constructed by quantum dots with various diameters, were obtained by a potentiostatic electrodeposition method at room temperature. The structural, optical, surface morphology, compositional analysis and Raman spectra properties of the deposited films have been studied using X-ray diffraction, optical absorption with scanning electron microscopy, EDAX, and Raman spectroscopy. The electrolyte concentration and deposition time can be used to control the diamete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 17 publications
2
14
0
Order By: Relevance
“…Dhasada et al [4] reported band gap value of copper telluride thin films varies in the range from 2.74 to 2.89 eV which is closer to the band gap value reported in the present work. The observed change in the optical band gap may be due to the improvement in crystallinity, formation of various phases and the variation in the stoichiometry of the films.…”
Section: Accepted Manuscriptsupporting
confidence: 89%
See 1 more Smart Citation
“…Dhasada et al [4] reported band gap value of copper telluride thin films varies in the range from 2.74 to 2.89 eV which is closer to the band gap value reported in the present work. The observed change in the optical band gap may be due to the improvement in crystallinity, formation of various phases and the variation in the stoichiometry of the films.…”
Section: Accepted Manuscriptsupporting
confidence: 89%
“…% of copper present in the film deposited at 300 ºC compared to the film deposited at RT and 200 ºC. Dhasade et al[4] obtained higher…”
mentioning
confidence: 96%
“…This findings suggest the combination of two metals might be making either n‐type or p‐type semiconductor in CuTe/GP which makes it suitable for showing enhanced electrocatalytic activity in comparison with Cu/GP and Te/GP electrodes. Here combined system Cu and Te makes an alloy which is a semiconductor having band gap value 2.7 eV [28a]. Discussing the exact role of of Cu or Te in CuTe nps for simultaneous electrochemical detection of EP and UA needs more detailed work and now it is beyond the scope of this paper.…”
Section: Resultsmentioning
confidence: 99%
“…Various methods have been developed for the synthesis of copper telluride, including hydrothermal, solvothermal, ion-exchange, vacuum-deposition, and electrodeposition techniques (Zhang et al, 2006;Dhasade et al, 2012;Kriegel et al, 2013;Nethravathi et al, 2014;Bhuvaneswari et al, 2017). Hydrothermal synthesis involves the decomposition of reactants or chemical reactions between them at high temperature and high pressure in an aqueous solution, while solvothermal synthesis is similar but involves a non-aqueous solvent (Nethravathi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%